In vitro antiviral activity of Lactobacillus plantarum using SPF embryonated eggs and hemagglutination assay (Bangladesh Journal of Pharmacology, 2015)
Serum pathogen-free (SPF) embryonated egg for culturing virus has three main steps: a) candling of egg, b) inoculation of egg and c) harvesting of inoculated egg. Furthermore, hemagglutination assay consists of only one step. The method is easy to perform. However, this experiment must be performed in a class 2 biosafety cabinet. VIDEO CLIPSIn vitro antiviral activity test using SPF embryonated eggs:   7.5 minHemagglutination test:                                                    7.3 min